2014
DOI: 10.1093/chromsci/bmu049
|View full text |Cite
|
Sign up to set email alerts
|

Simplified Procedure of Silymarin Extraction from Silybum marianum L. Gaertner

Abstract: Silymarin, a mixture of flavonolignans exhibiting many pharmacological activities, is obtained from the fruits of milk thistle (Silybum marianum L. Gaertner). Due to the high lipid content in thistle fruits, the European Pharmacopoeia recommends a two-step process of its extraction. First, the fruits are defatted for 6 h, using n-hexane; second, silymarin is extracted with methanol for 5 more hours. The presented data show that this extremely long traditional Soxhlet extraction process can be shortened to a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 14 publications
1
36
1
1
Order By: Relevance
“…Its use of solvents at elevated pressure, i.e., temperatures above the boiling points, increased the dynamic of the extraction; enhanced analyte diffusion through cell walls; and decreased solvent viscosity and surface tension. Acetone was used as an extraction solvent as it has been reported to produce the highest silymarin yield (Wianowska and Wiśniewski, 2015). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use of solvents at elevated pressure, i.e., temperatures above the boiling points, increased the dynamic of the extraction; enhanced analyte diffusion through cell walls; and decreased solvent viscosity and surface tension. Acetone was used as an extraction solvent as it has been reported to produce the highest silymarin yield (Wianowska and Wiśniewski, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Accelerated Solvent extraction was carried out with a Dionex ASE350 instrument (Dionex Corporation, Sunnyvale, CA, USA) according to a reported method (Wianowska and Wiśniewski, 2015) with modifications. The whole ground fruits (1 g) was placed into a 34-ml stainless steel extraction cell containing filter paper at the bottom.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the interesting source of valuable biologically active substances seems to be young shoots, in which Maietti et al found the flavonoids content, from 517 to 2698 μg/g fresh weight, depending on the plant variety [21]. The solvent type is an important factor in the extraction process, having a major impact on the antioxidant activity of obtained plant extracts [31,32]. In our study, three polar alcohols (methanol, ethanol and isopropanol) differing, inter alia, in the length of the molecule carbon chain were used as solvents.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to eliminate the drawbacks of the conventional liquid extraction and to enhance the extraction process and, make it more environmentally friendly, the innovative extraction methods such as microwave-, ultrasound-, pressure-, and enzyme-assisted extraction together with supercritical fluid extraction have been developed and introduced. Their applicability for the isolation of various plant constituents, including CQAs, both on a small (laboratory) and large (manufactering) scale, is increasingly growing (Kaufmann and Christen 2002;Waksmundzka-Hajnos et al 2004;Li et al 2005;Carabias-Martinez et al 2005;Dawidowicz and Wianowska 2005a, b;Wianowska et al 2009Wianowska et al , 2014aWianowska et al , b, 2015bMustafa and Turner 2011;Upadhyay et al 2012;Dent et al 2015;Wianowska and Wiśniewski 2015;Tena et al 2015;Wianowska and Dawidowicz 2016a, b;Srinath and Maheswari 2016). This is understandable as these techniques, by limiting the use of mostly toxic organic solvents could improve extracts quality additionally, which is important taking into account the CQAs applicability as pro-health additives to foods and supplements.…”
Section: Isolation Of Caffeoylquinic Acidsmentioning
confidence: 99%